Laryngopharyngeal reflux as a potential cause of Eustachian tube dysfunction in patients with otitis media with effusion - Zhen, Zhen; Zhao, Tingting; Wang, Quangui; Zhang, Junbo; Zhong, Zhen (Frontiers in Neurology, 2022)
Objective: To explore the association between laryngopharyngeal reflux disease (LPRD) related symptoms and the eustachian tube (ET) function in adult patients with otitis media with effusion (OME). Materials and methods: A total of 105 adult patients with OME were retrospectively studied. All these patients had undergone tubomanometry (TMM) test for the affected ears before treatments. The LPRD related symptoms were all assessed by the Reflux Symptom Index (RSI) scale. Results: Among the 105 included patients, the numbers of subjects with only one and both two ears affected were 65 (57.1%) and 40 (42.9%), respectively. Therefore, a total of 145 affected ears were studied. For these affected ears, a linear regression analysis that included sex, age, BMI, smoking history, drinking history, RSI value, and the condition of the contralateral ear suggested that only RSI value was significantly associated with TMM value (P<0.001), with the correlation coefficient of -0.112. Among the 9 symptoms in RSI scale, affected ears with the following symptoms (vs. affected ears without) showed significantly lower TMM values: excess throat mucus or postnasal drip, difficulty swallowing food, liquids, or pills, and sensations of something stuck in your throat or a lump in your throat (all P<0.05). Conclusion: LPRD may disrupt ET function in adult OME patients. A higher RSI score is independently predictive for a bad ET patency in such patients, and is indicative for an additional anti-reflux therapy.